Factors Affecting the Compliance of National Health Insurance Participants Segment of Non-Wage Recipients in Paying the Contributions - Franky Vinansius Marpaung; Mappeaty Nyorong; Tengku Moriza (Newinera Publisher, 2022)
This study's objective is to investigate the variables influencing the compliance of the National Health Insurance (JKN) Participant Segment of Non-Wage Recipients (PBPU) in Paying JKN Contributions in the BPJS Health Work Area, North Tapanuli Regency. This sort of research is quantitative and employs a cross-sectional study design. This study's population consists of all Non-Wage Recipient Workers (PBPU) in Siborong-borong District, North Tapanuli Regency, a total of 12,323 persons, with a sample size of 99 calculated using a purposive sampling technique. The study used univariate, bivariate, and multivariate techniques. The findings of the chi-square test indicated that education (p = 0.066> 0.05), occupation (p = 0.008 0.05), knowledge (p = 0.003 0.05), income (p = 0.000 0.05), and distance (p= 0.0010.05) were significantly correlated with each other. The logistic regression test reveals that income, with an Exp (B) value of 4,778, has the greatest impact on compliance with making JKN payments. This research concludes that employment, knowledge, income, and distance have a link with JKN contribution compliance, however education has no association with JKN contribution compliance. The community need socialization in order to raise public understanding and awareness of their monthly obligation to make JKN payments.